Equity of health resource distribution in China during 2009–15: an analysis of cross-sectional nationwide data. (December 2017) - Xie, Xiaoxu; Liu, Peng; Zheng, Yan; Zhou, Weimin; Zou, Jiaojiao; Wang, Xiaohong; Wang, Long; Guo, Tongjun; Ma, Xu; He, Yuan; Chen, Yixin
Abstract: Background: In 2009, China initiated health-care reforms, which aimed to provide affordable and accessible medical care for the country's entire population by 2020. We aimed to analyse the equity of the distribution of China's health resources since the health-care reform. Methods: In this analysis of nationwide data, we obtained data about China's health resources and wealth by province for the years 2009–15 from the China Statistical Yearbooks and Chinese National Health and Family Planning Commission Yearbooks published by the Chinese Government. We calculated concentration indexes based on population size to evaluate the equity of resource allocation according to wealth (assessed by per-capita gross domestic product). Concentration index values range from −1 to 1; 0 indicates absolute equity. A negative value means that resources are concentrated within poorer populations, whereas a positive value indicates that resources are concentrated within richer populations. Findings: During 2009–15, hospital beds were concentrated in richer regions (concentration index range 0·0202 to 0·0587 [minimum to maximum values obtained during 2009–15]) and primary care sector beds were concentrated in poorer regions (−0·0955 to −0·0581). The concentration index for hospitals changed from 0·0037 in 2009 to −0·298 in 2015, indicating a trend in hospital concentration moving from richer to poorer areas. The primary care sector consistently concentrated in poorer regions (concentration index range −0·0848 to −0·0646). Total health expenditure (0·1201 to 0·1481), including paid by government (0·0285 to 0·0623), society (0·2048 to 0·2496), and individuals (0·0828 to 0·1170), concentrated in richer regions. Health workers (0·0325 to 0·0555) and physicians (0·0758 to 0·0909) also concentrated in the richer regions. Interpretation: The distribution of China's health resources is equitable, but human health resources and financial health resources were more concentrated in richer regions. An increase in the concentration of well resourced hospitals in richer regions and poorly resourced primary care institutions in poorer regions might further enlarge the health-care utilisation gap between rich and poor populations. Funding: National Key Research and Development Program of China (2016YFC1000102, 2016YFC1000307), and the National Natural Science Foundation of China (81602854).